EARLY DIAGNOSTIC CRITERIA OF RENAL INJURY AND COORDINATION OF TREATMENT IN PATIENTS WITH CHRONIC HEART FAILURE - G. A., Atakhodjayeva; Z.T. , Korakulova (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aimed to examine the clinical, functional, echocardiographic, and biomarker characteristics of chronic heart failure (CHF) patients with and without renal dysfunction, given the frequent coexistence of both conditions and their complex management challenges. Method: A total of 129 CHF patients were evaluated and divided into two groups based on renal function. Clinical symptoms, six-minute walk test results, echocardiographic findings, and serum biomarker levels were compared. Results: Patients with renal dysfunction exhibited more severe symptoms, higher Clinical State Scale scores, shorter walking distances, and more advanced diastolic failure with greater ventricular remodeling. NT-proBNP, NGAL, KIM-1, and cystatin C levels were significantly elevated in the renal dysfunction group, whereas creatinine showed only minor increases. This discrepancy indicates the limited sensitivity of traditional renal markers in detecting early tubular injury. Novelty: The study highlights the diagnostic value of novel renal biomarkers in CHF patients, demonstrating their potential for early detection of subclinical kidney damage and improved risk stratification, ultimately contributing to timely interventions and better prognostic outcomes.